2021
DOI: 10.1002/tox.23104
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0001073 targets miR‐626/LIFR axis to inhibit lung cancer progression

Abstract: Circular RNAs (circRNAs) are associated with lung cancer progression. However, it is unclear whether and how circRNA hsa_circ_0001073 (circ_0001073) are involved in lung cancer progression. circ_0001073, microRNA (miR)-626, and leukemia inhibitory factor receptor (LIFR) abundances were determined via quantitative reverse transcription polymerase chain reaction or western blot. Cell viability, invasion, and apoptosis were analyzed by cell counting kit-8, transwell analysis and flow cytometry, respectively. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Among the ligands of LIFR, LIF is overexpressed and has been identified playing a tumor-promoting role in various tumors, including prostate, nasopharyngeal, breast, gastric, endometrial, colorectal, melanoma, osteosarcoma, lung and pancreatic cancers (2)(3)(4)(5)(6)(7)(8)(9)(10). Recently, increasing numbers of studies have been exploring the cancer type-specific role of LIFR in these cancers (11)(12)(13)(14)(15)(16). LIFR is expressed in a variety of organs and cell types and is involved in angiogenesis, cancer progression, development and regulation of stem cells (2,4,10,17).…”
Section: Introductionmentioning
confidence: 99%
“…Among the ligands of LIFR, LIF is overexpressed and has been identified playing a tumor-promoting role in various tumors, including prostate, nasopharyngeal, breast, gastric, endometrial, colorectal, melanoma, osteosarcoma, lung and pancreatic cancers (2)(3)(4)(5)(6)(7)(8)(9)(10). Recently, increasing numbers of studies have been exploring the cancer type-specific role of LIFR in these cancers (11)(12)(13)(14)(15)(16). LIFR is expressed in a variety of organs and cell types and is involved in angiogenesis, cancer progression, development and regulation of stem cells (2,4,10,17).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in AML, hsa_circ_0001947 can inhibit disease progression by regulating the hsa-miR-329-5p/CREBRF axis, 15 while circ_0006404 enhances the progression of prostate cancer progression via the miR-1299/CFL2 axis, 16 and hsa_circ_0001073 can suppress the progression of lung cancer via modulating miR-626/LIFR axis signaling. 17 In previous studies, hsa_circ_0079480, which is encoded on chr7:16298014-16317851, has been identified as an oncogenic driver of AML capable of promoting tumor progression through the miR-654-3p/HDGF regulatory axis. 18 The clinical importance of serum hsa_circ_0079480 in AML patients, however, has yet to be established, and this study was therefore designed to examine the prognostic value of hsa_circ_0079480 levels in the serum of individuals with AML.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, circRNAs can bind to specific microRNAs (miRNAs) in a sequence‐specific manner, thereby serving as competing endogenous RNAs (ceRNAs) to prevent miRNA‐mediated repression of mRNA expression. For example, in AML, hsa_circ_0001947 can inhibit disease progression by regulating the hsa‐miR‐329‐5p/CREBRF axis, 15 while circ_0006404 enhances the progression of prostate cancer progression via the miR‐1299/CFL2 axis, 16 and hsa_circ_0001073 can suppress the progression of lung cancer via modulating miR‐626/LIFR axis signaling 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CircRNAs are available to perform as a sponge of microRNAs (miRNAs) and indirectly modulate downstream genes, thus mediating the metastasis and other biological functions of cancer cells [ 9 , 10 ]. For instance, circ_0001073 is reported to repress LC advancement via miR-626/LIFR axis, clarifying the latent value of circ_0001073 in LC therapy [ 11 ]. Meanwhile, a study proposes that circ-CCS is elevated in LC and forecasts unpleasing prognosis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%